Diffusion coefficients of chlorophenols in water by computer simulation - Parreira, M. Cristina B. (2013)
Cholophenols have found extensive industrial applications as wood preservatives or intermediated compounds for pesticide synthesis, and are also by-products of wood pulp bleaching processes [1]. As a result, they are nowadays common natural water contaminants, being considered priority substances by recent European Directives for Environmental Protection, due to their toxicity and persistence. The establishment of theoretical models to study environmental fate of chlorophenols is an important scientific topic. On the other hand, some unit operations are used to remove them from wastewater, such as adsorption [2] and reverse osmosis [3]. In both approaches, the knowledge of some key properties is needed, such as diffusion coefficients in water. Despite of their obvious importance, the diffusion coefficients of chlorophenols in water are scarce in literature and in many cases have to be estimated. Computer simulation can provide a way to systematically estimate this parameter for chlorophenol chemical family.